An enantioselective assembly of naphthopyran via NHC-catalyzed [3 + 3] annulation of bromoenal with β-tetralone. Issue 2 (12th December 2018) - Li, Sha; Yao, Yibiao; Tang, Ziwei; Sun, Baomin; Yu, Chenxia; Li, Tuanjie; Yao, Changsheng
Abstract : An asymmetric assembly of naphthopyran was realized via the N-heterocyclic carbene (NHC)-catalyzed formal [3 + 3] annulation of bromoenal and β-tetralone. The key advantages of this protocol include ready availability of starting materials, mild reaction conditions, good yields. Abstract : An asymmetric assembly of naphthopyran was realized via the N-heterocyclic carbene (NHC)-catalyzed formal [3 + 3] annulation of bromoenal and β-tetralone. The key advantages of this protocol include ready availability of starting materials, mild reaction conditions, good yields and excellent enantioselectivities.